Pelatihan Perhitungan Harga Pokok Produksi untuk Meningkatkan Daya Saing UMKM di Padang Tae Ampiang Parak Pesisir Selatan - Luciana Luthan; Rika Sarfika; Ezi Anggraini (Warta Pengabdian Andalas, 2022)
The correct calculation of the cost of production is essential for a manufacturing business. The accuracy of the calculation can increase business competitiveness through a cost leadership strategy. This activity aimed to provide training in determining the cost of production in Umi Wiwik's business by using a comparative analysis of variable and complete costing methods. This activity was carried out at the Umi Wiwik business in Padang Tae Ampiang Parak, Sutera Sub-district, Pesisir Selatan, West Sumatra. The method used descriptive analysis by applying variable costing and complete costing to calculate the cost of production of tuna nuggets and tuna meatballs. The community engagement activity was carried out by presentation, discussions and exercises for 15 participants. The calculation result showed significant differences between variable costing and full costing implementation. The cost of production using the variable costing method is lower than the entire costing method. It allows Umi Wiwik's business to set the selling price of tuna nuggets and meatballs at a lower price, with the same profit target, than competitors and make it more attractive to potential consumers.